El problema de las Aquae calidae del norte del conventus Tarraconensis (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Although epigraphic sources attest only one city with the name Aquae calidae in the North of the conventus Tarraconensis, literary sources mention two different locations with the same name. The analysis of the available information allows to identify the name Aquae calidae with Caldes de Malavella in epigraphic texts, while literary sources would allude to Caldes de Malavella and Caldes de Montbui, possibly by the confusion between both cities because of homonymy.
Keywords: Epigraphy; Roman History; Caldes de Montbui; Caldes de Malavella; Aquae calidae; Ptolemy; Pliny the Elder; Hispania